Preface (Baltic Journal of Sport and Health Sciences, 2026)
This supplement is published in conjunction with the 16th HEPA Europe conference 2025, held within the HEPA Europe network, which the WHO Regional Office established to advance the agenda of health-enhancing physical activity. This year also marks the 20th anniversary of HEPA Europe, commemorating two decades since its inaugural meeting in 2005 in Gerlev, Denmark. Over these twenty years, the network has served as a key forum for advancing research, policy, and practice related to health-enhancing physical activity, ultimately promoting better health and wellbeing across the WHO European Region.To celebrate HEPA’s anniversary, the Chair of HEPA Europe, Dr. Alexis Lion, together with co-authors, prepared a publication that reviews two decades of HEPA Europe’s activities. The article not only provides a descriptive overview but also a critical reflection on the first 20 years of HEPA Europe, evaluating its achievements, challenges, and future priorities. Moreover, it offers valuable insights into how regional health promotion networks can adapt and remain effective in a changing policy and public health landscape.The HEPA Europe 2025 conference in Kaunas city (Lithuania) will focus on “Health Enhancing Physical Activity: Taking Steps Towards Sustainability”. This conference aims to bring together a vibrant community of scientists, leading experts, policymakers, professionals, and stakeholders to discuss, share, and develop innovations that connect research with practical applications in health-enhancing physical activity. Participants will have the opportunity to explore the latest advancements in science, policy, and practice. This gathering will encourage collaboration to drive impactful change across Europe and beyond.At this year’s conference, three experts will address our theme from different perspectives. Assoc. Prof. Dr. Brigita Miežienė (Lithuanian Sports University, Kaunas, Lithuania) will share her insights on “Healthy Moves: Exploring the Socio-Ecological Approach to Active Transport – How Far Can We Go Together?”. Assoc. Prof. Dr. Peter Gelius (University of Lausanne, Lausanne, Switzerland) will delve into “Pillars, Doughnuts, Wedding Cakes: Multidimensional Models of Sustainability and Their Implications for Physical Activity”. Finally, Francesca Racioppi (World Health Organization European Centre for Environment and Health, Bonn, Germany) will conclude with her presentation titled “Race to the Finish: Our Evolving Understanding of the Role of Active Mobility for a Sustainable Future”.Over 380 participants from 40 countries will take part in 22 symposia, featuring 90 presentations, and 204 oral and pitch presentations that encompass research, practice, and policy perspectives. Oral presentations are organised into 26 themes, covering topics from sustainability to healthy, active living and policy, all led by seasoned experts in their fields, and pitch presentations are organised into two sections. This diverse array of themes showcases the extensive expertise of researchers, practitioners, and policymakers in health-enhancing physical activity. We encourage delegates to attend sessions that align with their specific areas of expertise while also exploring themes that are less familiar to them. We hope that this approach will foster the sharing and blending of ideas across different sectors and inspire creativity through mutual learning.